2024
DOI: 10.1021/acsami.4c00452
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanofibrous Aerogels Derived from Electrospun Polyimide for Multifunctional Piezoresistive Sensors

Jun Lin,
Jianwei Li,
Yutong Song
et al.

Abstract: The fabrication of carbon aerogels with ultralow density, high electrical conductivity, and ultraelasticity still remains substantial challenges. This study utilizes electrospun polyimide aerogel as the source to fabricate flexible carbon nanofibrous aerogel (PI-CNA) capable of multifunctional applications. The lightweight PI-CNA based piezoresistive sensor shows a wide linear range (0−217 kPa), rapid response/recovery time, and fatigue resistance (12,000 cycles). More importantly, the superior pressure sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Finally, Table 1 presents a comparison of the performance of the PEDOT:PSS@PI sensor in this study and the piezoresistive pressure sensors that were recently reported. 27,42,43,54,61,64–66 Our PEDOT:PSS@PI sensor exhibits fast response times, along with a high gauge factor of up to 4.06, and provides a wide measuring range spanning approximately 0 to 80%, equivalent to roughly 250 kPa. This suggests that the created sensor is suitable for measuring both gentle pressure and significant forces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Table 1 presents a comparison of the performance of the PEDOT:PSS@PI sensor in this study and the piezoresistive pressure sensors that were recently reported. 27,42,43,54,61,64–66 Our PEDOT:PSS@PI sensor exhibits fast response times, along with a high gauge factor of up to 4.06, and provides a wide measuring range spanning approximately 0 to 80%, equivalent to roughly 250 kPa. This suggests that the created sensor is suitable for measuring both gentle pressure and significant forces.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, PI nanofiber-based pressure sensors have been extensively documented. 9,43–45 For instance, Shaohua et al produced electrospun PI fiber-coated silver nanowire (AgNW) sponges, 44 while Lei et al produced an elastic aerogel made of Ti 3 C 2 T x MXene with 3D “lamella-pillar” microporous structures, achieved by cross-linking and intercalating electrospun polyimide nanofibers (PINFs). 45 These materials exhibited weak fiber interactions, resulting in limited mechanical characteristics (with a maximum strain of 50% and a maximum stress of approximately 3.5 kPa) and a constrained detection range, reaching only a compressive strain of up to 50%, corresponding to 8 kPa of stress, respectively.…”
Section: Introductionmentioning
confidence: 99%